SISTEM INFORMASI PEMESANAN PAKET PERNIKAHAN PADA LARASATI GRIYA RIAS DAN DEKORASI - , NESSYA ALVIORIZA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
dan Dekorasi only made through manual recording in the reservation book. This recording method is quite suffice enough, but less effective and efficient because it cannot be transformed into a report. Furthermore, it is harder to check all the transaction. Therefore, a web based information system of wedding packages ordering service is needed for Larasati Griya Rias dan Dekorasi in order to improve service for customerâs satisfaction. The purpose of making this information system is to provide a solution to the problems mentioned above. This web based information system is expected to ease the process of ordering a wedding package into something that is simple, straightforward, and practical needs. It is essential, especially to cope with competition in the world of wedding organizer. Also this information system can help spreading information, managing order, and help to ease customers to do the ordering process. This information system is created using HTML programming language, Javascript, jQuery PHP, and MySQL database server.